CONGESTION CONTROL AND LOAD BALANCED ROUTING USING DYNAMIC PROGRAMMING FOR WIRELESS AD HOC NETWORKS - HABIB, IFFAT (2016)
Ad hoc networks consist of mobile devices such as mobile phones, tablets, laptops, that are connected over a wireless medium. Most of the existing routing protocols for wireless ad hoc networks follow the shortest path or minimum distance as the route selection criteria. This type of routing is called shortest path routing (SPR). However, the shortest path does not balance the traffic load on all nodes in a network. When multiple users use the shortest path for data transfer, some nodes may be overloaded with data forwarding and the wireless links get more data traffic than they ran handle The congestion nan hp decreased by careful distribution of data traffic on all available links. This technique is called load-balancing. Existing literature on load-balancing considers certain parameters for congestion measurement. These include the length of the queue, MAC utilization, queuing delay, transmission delay, packet drop rate, etc. The congestion is usually measured at a node or at the link. However, the combination of nodal and link congestion is necessary for accurate congestion estimation